CD4(+) cell count and risk for antiretroviral drug resistance among women using peripartum nevirapine for perinatal HIV prevention - Dorton, Benjamin J. (2010)
OBJECTIVE: To determine the association between antenatal CD4(+) cell count and development of viral drug resistance following use of peripartum nevirapine (NVP) for perinatal HIV prevention. DESIGN: Secondary analysis of data from previously conducted randomized control trial. SETTING: Lusaka, Zambia. POPULATION: HIV positive pregnant women. METHODS: We analyzed data from a clinical trial of single-dose tenofovir/emtricitabine (TDF/FTC) to reduce viral drug resistance associated with peripartum NVP. The trial population was categorized according to antenatal CD4(+) cell count (200–350 cells/uL, 351–500 cells/uL, and >500 cells/uL). MAIN OUTCOME MEASURES: Relative risk for acquiring drug resistance—determined by consensus sequencing and oligonucleotide ligation assay (OLA)—was estimated using multivariable logistic regression. RESULTS: Of 397 study participants, 119 (30%) had a CD4(+) count of 200–350 cells/uL, 135 (34%) had a CD4(+) count of 351–500 cells/uL, and 143 (36%) had a CD4(+) count >500 cells/uL. Among women receiving no intervention, risk for drug resistance appeared to increase as CD4(+) cell count decreased. Participants with CD4(+) cell counts of 200–350 cells/uL randomized to the study arm had the lowest risk, suggesting higher efficacy of the intervention within this stratum. These results were consistent at two and six weeks, regardless of how drug resistance was measured. CONCLUSION: Women with CD4(+) cell counts of 200–350 cells/uL may be at increased risk for viral drug resistance following use of peripartum NVP. Given the high prevalence of NVP resistance and the clear benefits of treatment, antiretroviral therapy should be initiated among pregnant women with CD4+ cell counts ≤ 350 cells/uL.